Effect of the environment on the physiological responses of goats raised in hot weather receiving different sources of roughage (Research, Society and Development, 2023)
The objective was to evaluate the effects of the environment through the physiological responses of mixed breed goats, under semi-arid conditions in Santana do Ipanema. Thirty goats aged one year old and average weight between 24 and 28 kg were used. The following parameters were studied: rectal temperature (TR) where a clinical thermometer was introduced directly from the animal's rectum, respiratory rate (RR) obtained by indirect auscultation of heart sounds. The beats were obtained with a stethoscope placed directly on the left thoracic region, counting the number of beats during 20 seconds. Air temperature and relative humidity were recorded using a portable psychrometer in the experimental area. Physiological and environmental parameters were recorded every 3 hours. Blood samples from each animal were taken every 8 days, performing the erythrogram (red blood cell count, hematocrit and hemoglobin), and the leukogram (total leukocyte count). The data obtained were statistically evaluated using the Tukey test at a significance level of 5%. It was observed that the TR was not affected by the diets, remaining above the normal range in all diets. The RR and HR suffered a significant effect (p< 0.05) also remaining above the ideal. The histogram showed segmented lymphocytes, monocytes and rods with significant differences, but within the ideal range for the species. It can be concluded that the observed parameters were more influenced by the climate than the source of roughage, making it safe to use all the studied diets.